2009
DOI: 10.1080/00016480802032777
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory viruses in nasopharyngeal secretions and middle ear fluid from children with acute otitis media

Abstract: Respiratory viruses were detected in 360 of 1092 NPS specimens, including 157 isolates of respiratory syncytial virus and 88 of influenza virus. Among 1092 MEF specimens, 102 were virus-positive, including 43 for respiratory syncytial virus and 29 for influenza virus. In 75 children, respiratory viruses were only detected in MEF. The viral detection rate was higher in children with fever at an early stage of their illness. The tympanic membrane changes associated with viral infection tended to be less severe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…It has also been shown that about one-third of children with viral URI developed AOM within 4 weeks of its onset [7]. Using conventional and molecular diagnostics, respiratory viruses have been detected from the nasopharynx in the majority of cases and in up to 70 % of the middle ear fluid (MEF) from children presenting with AOM [811]. It is notable that tympanic membrane changes in AOM can be observed as early as the first day of symptomatic viral URI [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that about one-third of children with viral URI developed AOM within 4 weeks of its onset [7]. Using conventional and molecular diagnostics, respiratory viruses have been detected from the nasopharynx in the majority of cases and in up to 70 % of the middle ear fluid (MEF) from children presenting with AOM [811]. It is notable that tympanic membrane changes in AOM can be observed as early as the first day of symptomatic viral URI [12].…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed 71 fulltext articles, of which 12 were included (Supplemental Fig 3). 12,18,21,30,[35][36][37][38]41,[43][44] …”
Section: Aommentioning
confidence: 99%
“…Treatment failures and relapses of AOM in children are influenced not only by microbiological factors, such as antibiotic resistance (10), viral coinfection (16,17), biofilm formation (11,12), and invasion of epithelial cells (18), but also by host factors, including immaturity of the immune system (17), lack of breastfeeding (19), tubal dysfunction (20), recent antibiotic usage (21), and multiple episodes of AOM. In addition, environmental factors such as attending a day care center (2) and the presence of siblings (22) influence treatment failure and relapse of AOM.…”
Section: Discussionmentioning
confidence: 99%